Governance Capacity and Subnational Variation in Child Protection: Evidence from Indonesia’s Index - Inka Winarni Mufdhalifah; Mala Sondang Silitonga (Jurnal Publikasi Ilmu Manajemen, 2026)
This study aims to analyze governance capacity and subnational variation in child protection performance in Indonesia based on the Child Protection Index, Child Rights Fulfillment Index, and Special Child Protection Index. The study employed a quantitative cross-sectional design covering 38 Indonesian provinces, using descriptive statistics, quadrant analysis, correlation analysis, and multiple linear regression. The findings reveal substantial variation in child protection achievements across provinces, with out-of-school children emerging as the most consistent structural vulnerability factor negatively affecting the Special Child Protection Index. Stunting and child poverty also show negative relationships, although their effects are weaker than the education-related factor. These findings indicate that child protection performance is not determined solely by national policy frameworks, but also by local government capacity to integrate education, health, social, legal, and child protection services. The implication is that local governments need to strengthen integrated child protection systems, prioritize out-of-school children, and use accurate data to design more responsive and equitable child protection policies.